Media Sosialisasi Penerimaan Dalam Meningkatkan Recruitment Calon Mahasiswa Baru - Suryani Suryani (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2021)
The higher education admission selections are intended to obtain excellent prospective students. The opportunities are given to all students who graduated from senior high, vocational and Islamic senior high, and Islamic boarding schools (Dayah) throughout Lhokseumawe. These activities involved some lecturers and academicians from The State Islamic Institute (IAIN) Lhokseumawe located in Alu Awee, Muara Dua District, Lhokseumawe City. The methods used in the SPMB socialization process were discussion and feedback to create two-way interactions. This socialization was intended that the senior high, Islamic High and Islamic boarding school students now at the end of their study can smoothly participate in SPMB, to educate the students who will soon become the prospective students to easily make their registrations by fulfilling the required conditions and determine their majors when registering SPMB in accordance with their interests. Keywords: Sosialization, Discussion